Plasma pentosidine as a useful biomarker of sarcopenia, low gait speed, and mortality in patients with cirrhosis - Saeki, Chisato; Saito, Mitsuru; Tsubota, Akihito (Frontiers in Medicine, 2023)
Purpose The accumulation of advanced glycation end products (AGEs) is associated with various diseases and age-related impairments, including loss of muscle mass and function. We investigated the association between plasma pentosidine, which is one of the AGEs, and sarcopenia, low gait speed, and mortality in patients with cirrhosis. Methods This retrospective study divided 128 patients with cirrhosis into three groups by 25th and 75th quartiles of baseline plasma pentosidine levels: low (L)-, intermediate (I)-, and high (H)-pentosidine (Pen) groups. Sarcopenia was diagnosed following the Japan Society of Hepatology criteria. Low gait speed was defined as <0.8 m/s. The cumulative survival rates were compared between the three groups. Cox proportional hazards regression analysis was performed to identify independent factors associated with mortality. Results Of the 128 patients, 40 (31.3%) and 34 (26.6%) had sarcopenia and low gait speed, respectively. The prevalence of sarcopenia and low gait speed significantly increased stepwise with increasing plasma pentosidine levels, with the highest in the H-Pen group (59.4% [19/32] and 56.3% [18/32], respectively) and lowest in the L-Pen group (18.8% [6/32] and 6.3% [2/32], respectively). Multivariate analysis identified plasma pentosidine levels as a significant and independent factor associated with sarcopenia (odds ratio [OR], 1.07; p = 0.036) and low gait speed (OR, 1.06; p = 0.036), with the cutoff levels of 0.0792 μg/mL (sensitivity/specificity, 0.600/0.773) and 0.0745 μg/mL (sensitivity/specificity, 0.735/0.691), respectively. The cumulative survival rates were significantly lower in the H-Pen group than in the L-Pen (hazard ratio [HR], 11.7; p = 0.001) and I-Pen (HR, 4.03; p < 0.001) groups. Plasma pentosidine levels were identified as a significant and independent prognostic factor (HR, 1.07; p < 0.001). Conclusion Plasma pentosidine levels are associated with sarcopenia, low gait speed, and mortality and may serve as a useful surrogate biomarker for these clinical events in patients with cirrhosis.